Deteksi dini masalah psikososial pada penyakit kardiovaskular berbasis kearifan lokal - Tiffany, Egidia; Pratiwi, Arum; Pribadi, Dimas Ria Angga (Holistik Jurnal Kesehatan, 2026)
Background: The incidence of cardiovascular disease remains a global threat and is expected to increase to 23.3 million by 2030. In Central Kalimantan, the Dayak people have unique dietary characteristics that potentially influence cardiovascular risk, such as consuming high-fat meat, high-salt processed foods, and fermented foods. Purpose: To develop and evaluate a model for early detection of psychosocial problems in cardiovascular disease based on local wisdom. Method: This study used a mixed-methods approach with an action research design. The study was conducted at the Sebangau Kuala District Polyclinic with a sample of 88 participants. The nursing module was tested in a single 15-20 minute session. Cardiovascular risk levels were measured using the Socio-Cultural Cardiovascular Risk Assessment (SCCR), measuring cholesterol and blood pressure levels before and after the intervention. The local wisdom studied included culture, patterns, and dietary habits. Results: Based on the validity test, the 20 questions in the questionnaire were valid, with a calculated r value > r table (0.198). The correlation between each statement and the total score indicates a strong and significant relationship (p < 0.05), indicating that each item contributes to the construct being measured. Furthermore, the reliability test results showed a Cronbach's Alpha calculation of 0.988, indicating that the SCCR instrument has very high reliability (α > 0.9). The paired t-test results for the SCCR questionnaire showed a T-value of 10.154 with a probability of 0.001 (p < 0.001), a T-value of 9.795 for cholesterol levels with a probability of 0.001 (p < 0.001), and no significant changes in blood pressure with a T-value of -0.037 (p > 0.971). Conclusion: Early detection of psychosocial issues in cardiovascular disease based on local wisdom is effective in reducing the risk of cardiovascular disease in the Dayak community in Central Kalimantan, particularly through the provision of educational modules and changes in cholesterol levels. Suggestion: Healthcare institutions should integrate local cultural approaches into public health education programs.   Keywords: Cardiovascular Risk; Dayak Tribe; Early Detection; Local Wisdom.   Pendahuluan: Angka kejadian penyakit kardiovaskular masih menjadi ancaman di dunia dan diperkirakan semakin meningkat hingga 23.3 juta pada tahun 2030. Di wilayah Kalimantan Tengah, masyarakat suku Dayak memiliki karakteristik unik dalam pola makan mereka yang berpotensi memengaruhi risiko kardiovaskular, misalnya mengonsumsi daging tinggi lemak, olahan pakasem dan wadi yang tinggi garam, serta makanan berfermentasi. Tujuan: Untuk mengembangkan dan mengevaluasi model deteksi dini masalah psikososial pada penyakit kardiovaskular berbasis kearifan lokal. Metode: Penelitian ini menggunakan pendekatan mixed method dengan desain action research. Penelitian ini dilaksanakan di Poliklinik Kecamatan Sebangau Kuala dengan sample sebanyak 88 partisipan. Modul keperawatan diujikan dalam satu sesi dengan waktu 15-20 menit. Tingkat risiko kardiovaksular diukur menggunakan Socio-Cultural Cardiovascular Risk Assessment (SCCR), pengukuran kadar kolesterol serta tekanan darah sebelum dan sesudah intervensi. Kearifan lokal yang diteliti berupa culture, pola, dan kebiasaan makan. Hasil: Berdasarkan uji validitas, 20 item pertanyaan dalam kuesioner valid dengan hasil r hitung > r table (0.198) hitung 0.198. Nilai korelasi antara masing-masing pernyataan dengan total skor menunjukkan hubungan yang kuat dan signifikan (p-value < 0.05), sehingga setiap item berkontribusi terhadap konstruksi yang diukur. Selanjutnya, hasil uji reliabilitas menunjukkan perhitungan Cronbach’s Alpha sebesar 0.988 menunjukkan bahwa instrumen SCCR memiliki reliabilitas yang sangat tinggi (α > 0.9). Hasil uji paired t-test kuesioner SCCR menunjukkan nilai T 10.154 dan probabilitas 0.001 (p<0.001), nilai T kadar kolesterol sebesar 9.795 dan probabilitas 0.001 (p<0.001), dan tidak terdapat perubahan signifikan pada tekanan darah dengan nilai T -0.037 dan (p>0.971). Simpulan: Deteksi dini masalah psikososial pada penyakit kardiovaskular berbasis kearifan lokal efektif dalam menurunkan tingkat risiko penyakit kardiovaskular pada masyarakat suku Dayak di Kalimantan Tengah, terutama untuk pemberian edukasi menggunakan modul dan perubahan nilai kadar kolesterol. Saran: Institusi pelayanan kesehatan, sebaiknya mengintegrasikan pendekatan budaya lokal dalam program edukasi kesehatan masyarakat.   Kata Kunci: Deteksi Dini; Kearifan Lokal; Risiko Kardiovaskular; Suku Dayak.